2020
DOI: 10.1186/s12885-019-6481-8
|View full text |Cite
|
Sign up to set email alerts
|

Childhood maltreatment as a risk factor for cancer: findings from a population-based survey of Canadian adults

Abstract: Background: Childhood maltreatment (CM) is an established risk factor for various mental and substance use disorders. This study adds to existing evidence that CM may also be a risk factor for cancer. Methods: Based on data from a sample of 9783 men and 12,132 women from the 2012 Canadian Community Health Survey-Mental Health (CCHS-MH), this analysis explores mediated associations between cancer in adulthood and different levels of exposure to three types of CM-childhood physical abuse (CPA), childhood sexual … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 62 publications
(75 reference statements)
1
7
0
Order By: Relevance
“…The CM prevalences found here are in line with meta-analytic findings [ 48 ] as well as the result that CM-exposed individuals have a higher disease burden compared to non-exposed individuals is supported by previous evidence [ 49 51 ]. Given the association of CM to inflammatory processes [ 16 , 43 45 ], one mechanism possibly linking CM to diseases might be the biochemical clusters from study 1.…”
Section: Studysupporting
confidence: 92%
“…The CM prevalences found here are in line with meta-analytic findings [ 48 ] as well as the result that CM-exposed individuals have a higher disease burden compared to non-exposed individuals is supported by previous evidence [ 49 51 ]. Given the association of CM to inflammatory processes [ 16 , 43 45 ], one mechanism possibly linking CM to diseases might be the biochemical clusters from study 1.…”
Section: Studysupporting
confidence: 92%
“…Mental health problems Psychological distress was measured using the HSCL-10, which is primarily comprised of symptoms of anxiety and depression (31). The HSCL-10 addresses respondents' experiences during the previous 4 weeks of: (1) sudden anxiety, (2) anxiousness, (3) dizziness, (4) tension/stress, (5) self-blame, (6) sleeplessness, (7) sadness, (8) worthlessness, (9) nding everything burdensome, and (10) hopelessness. Each item was rated on a 4-point scale, from 1 "Not at all bothered" to 4 "Extremely bothered".…”
Section: Intimate Partner Violence and Childhood Violencementioning
confidence: 99%
“…It is estimated that approximately 30% of ever-partnered women have experienced physical and/or sexual violence at the hands of an intimate partner (1). Broad ranges of health outcomes, including mental health problems, have been associated with IPV among women (6)(7)(8). An early meta-analysis by Golding reported that suicidal ideation, substance abuse, post-traumatic stress disorder (PTSD), and depression were three to ve times more frequent among female victims of IPV when compared with non-victimized women (9).…”
Section: Introductionmentioning
confidence: 99%
“…Childhood and adolescence are pivotal developmental stages for the maturation of biological and behavioural systems, and CM can disrupt a child's development, increasing the risk of physical and mental health issues across the lifespan (Duncan et al, 2015 ; Guo et al, 2021 ; Halpern et al, 2018 ; Herrenkohl & Jung, 2016 ; Hovdestad et al, 2020 ; Humphreys et al, 2020 ; Kaufman & Torbey, 2019 ; Nakayama et al, 2020 ; Romano et al, 2015 ; Shields et al, 2016 ; Soares et al, 2020 ; Thompson et al, 2017 ; Ting et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%